Paris sketchbook - Brooks, Jason (Laurence King Publishing, 2013)
"The city of light, art, fashion and romance is brought to life through the stunning work of leading international fashion illustrator Jason Brooks in his Paris Sketchbook. During his time on fashion assignments at the couture shows, Jason developed a fascination for the city, drawing and painting beautiful travel journals that demonstrate his passion for all things Parisian. Bursting with insider fashion knowledge, insights on cafe culture and exquisite architectural details, Jason's whimsical take on Paris is part guidebook, part illustrated journal. It is a delicious armchair travelling experience that will transport you right into the centre of that sublime and dazzling city: Paris." -- Provided by publisher